Frontispiece: Multivalency Increases the Binding Strength of RGD Peptidomimetic‐Paclitaxel Conjugates to Integrin αVβ3. Issue 58 (17th October 2017) - Raposo Moreira Dias, André; Pina, Arianna; Dal Corso, Alberto; Arosio, Daniela; Belvisi, Laura; Pignataro, Luca; Caruso, Michele; Gennari, Cesare
Abstract : Multivalent binding is often used to increase the strength of ligand–receptor interactions. In oncology, the development of multimeric conjugates aims at promoting a more efficient recognition of target antigens, possibly leading to better therapeutic performance. The affinity for integrin αV β3 of multimeric conjugates ( cyclo [DKP‐RGD]) n ‐Val‐Ala‐PTX ( n =1–4) increases with the number of cyclo [DKP‐RGD] ligands up to n =3. For more information, see the Communication by L. Pignataro, C. Gennari et al. onpage 14410 ff.